ASUHAN KEPERAWATAN PASIEN DENGAN SIROSIS HEPATIS DEKOMPENSATA: PENDEKATAN MODEL ADAPTASI ROY [NURSING CARE FOR PATIENTS WITH DECOMPENSATED CIRRHOSIS: AN APPROACH USING ROY'S ADAPTATION MODEL] - Yulia Sihombing (Nursing Current: Jurnal Keperawatan, 2023)
Liver cirrhosis is a progressive chronic liver disease characterized by extensive degeneration and destruction of liver parenchymal cells. Patients with liver cirrhosis require quality management as the disease progresses and complications such as hepatic encephalopathy and upper gastrointestinal bleeding arises, which results in frequent hospitalizations. This study aims to obtain an overview of nursing care in an adult patient with decompensated liver cirrhosis using the Roy Adaptation Model. This research is a case study using the nursing process approach. Sampling was taken using purposive sampling technique. The results showed four nursing problems experienced by patients. There were three problems in physiological mode: ‘excess fluid volume’, ‘risk of bleeding’, ‘risk of injury’; and one problem in the role function mode which was ‘ineffective role performance’. The treatment given aimed to alleviate the condition, ability and participation of the patient/family members to manage the patient's condition. Skill enhancement of patients and family members the ability to manage health by patients and families facilitates the ability to adapt to changing health conditions as seen from the appropriate health behaviors displayed by patients and families. Providing health education and empowering health management by patients and their families by nurses are very important to improve adaptation thus  the quality of life of patients with cirrhosis of the liver.BAHASA INDONESIA ABSTRAK Sirosis hepatis adalah penyakit hati kronis progresif yang dicirikan oleh degenerasi luas dan destruksi sel-sel parenkim hati. Pasien sirosis hepatis membutuhkan manajemen kualitas hidup seiring perjalanan penyakit dan komplikasi yang timbul, yakni ensefalopati hepatikum dan perdarahan saluran cerna atas yang mengakibatkan pasien sering menjalani rawat inap. Penelitian ini bertujuan untuk mendapatkan gambaran asuhan keperawatan pada 1 pasien dewasa dengan sirosis hepatis dekompensata menggunakan Model Adaptasi Roy. Metode penelitian ini menggunakan studi kasus dengan pendekatan proses keperawatan. Pengambilan sampling menggunakan teknik purposive sampling. Hasil studi mengidentifikasi 4 masalah keperawatan yang dialami pasien yakni tiga masalah pada mode fisiologis: kelebihan volume cairan, risiko perdarahan, risiko cidera; dan satu masalah pada mode fungsi peran yakni tidak efektif performa peran. Penanganan yang diberikan bertujuan untuk meringankan kondisi, kemampuan dan partisipasi pasien/keluarga untuk mengelola kondisi pasien. Peningkatan kemampuan pengelolaan kesehatan oleh pasien dan keluarga memfasilitasi kemampuan adaptasi terhadap perubahan kondisi kesehatan yang terlihat dari perilaku kesehatan yang tepat yang ditampilkan oleh pasien dan keluarga. Tindakan pemberian edukasi kesehatan dan pemberdayaan pengelolaan kesehatan oleh pasien dan keluarga sangat penting dilakukan untuk meningkatkan kualitas hidup pasien dengan sirosis hepatis.